Sustainable Rating Systems for Infrastructure. - Dall’O’, Giuliano; Bruni, Elisa (Springer, 2020)
The use of any territory at various scales, from the national to the urban or neighbourhood, would not be possible if there were no infrastructures. Such infrastructure is composed of a variety of public and private physical attributions to improve that territory: these include various types of civil engineering structures, e.g., bridges, motorways, railways, airports but also energy and communication networks, just to mention a few examples. It plays a strategic role in the social, economic, environmental well-being of human beings but also of the ecosystems. To underline the importance of infrastructures, one of the Sustainable Development Goals of the U.N. (SDG 9) regards the development of quality, reliable, sustainable and resilient infrastructures. In the green planning of cities and communities, the topic of infrastructure must be examined with great attention. The purpose of this chapter is to address the issue of infrastructure by focusing on the relationship between international environmental sustainability protocols and infrastructure. The chapter will analyse in particular the international Envision® protocol, designed to certify the sustainability of infrastructures by presenting some examples of its application.
Keywords: Stadtsystem; Technische Infrastruktur; Verkehrsinfrastruktur; Umweltbewertung; Ökobilanz; Nachhaltigkeit; Zertifizierung; Nachhaltige Stadtentwicklung; Sustainable Development Goals